Mr. Popper's penguins - Atwater, Richard; Atwater, Florence (Little, Brown and Co., 1988)
The unexpected delivery of a large crate containing an Antarctic penguin changes the life and fortunes of Mr. Popper, a house painter obsessed by dreams of the Polar regions.